PENANAMAN SIKAP NASIONALISME DI MADRASAH IBTIDAIYAH - Ahmad Sholeh; Moch. Miftachur Rizki (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the students’ nationalistic attitudes, the classroom teachers’ efforts to instil an attitude of nationalism, and the obstacles faced by classroom teachers in instilling students' nationalistic attitudes at MI al-Ma'arif 04 Singosari Malang. It is because the spirit of nationalism has regressed. The research in this article used a descriptivequalitative approach to describe the phenomenon comprehensively through data collection and compiled in the narrative form. Data collection techniques used in-depth interviews, observation, and documentation. Furthermore, the data analysis used generally included data reduction, data presentation, and conclusion. The results showed that the students of Madrasah Ibtidaiyah already had an excellent nationalism attitude with an understanding of nationalism that was by the standards. To create this nationalist attitude in real, classroom teachers have tried it through 1)academic activities and 2) non-academic activities such as carrying out flag ceremonies, commemorating national days such as the Youth Pledge, Santri Day, and carrying out Scout activities. Meanwhile, the obstacles faced by classroom teachers in instilling an attitude of nationalism were meaningless and could be overcome. Hence, classroom teachers must continually improve in developing this nationalistic attitude in order to make the Indonesian nation to be strong with its unity and integrity.